Erythrocytic alpha-synuclein as potential biomarker for the differentiation between essential tremor and Parkinson’s disease - Yu, Zhenwei; Liu, Genliang; Zheng, Yuanchu; Huang, Guoshi; Feng, Tao (Frontiers in Neurology, 2023)
Introduction The differentiation between essential tremor (ET) and Parkinson’s disease (PD) can be difficult because of the symptom overlaps. Erythrocytes are the major source of peripheral α-synuclein (α-syn), which is the most studied pathological molecular of PD. We have reported that erythrocytic α-syn levels in PD patients are significantly increased compared to those in healthy controls (HCs). However, little is known about the levels of erythrocytic α-syn species in ET patients. Methods This study includes 15 patients with ET, 64 patients with PD, and 49 age and sex matched HCs. A well-established electrochemiluminescence assay was used to measure the erythrocytic total and aggregated α-syn levels. The receiver operating characteristic (ROC) curve analysis was applied to evaluate the diagnostic values of erythrocytic α-syn for ET diagnosis and differentiation. The correlations of erythrocytic α-syn levels with disease durations were tested using Spearman’s Rank Correlation analysis. Results We found that both erythrocytic total and aggregated α-syn concentrations are significantly increased in PD and ET patients compared to those in HCs. Erythrocytic total α-syn levels are significantly higher in ET patients than those in PD group. Furthermore, the ratios of erythrocytic aggregated to total α-syn levels in ET patients are significantly decreased than those in PD and HC subjects. We also found a significant association of erythrocytic aggregated α-syn levels with the disease duration of ET patients. Conclusion Our findings suggest new insight into the changes of erythrocytic total and aggregated α-syn levels as potential biomarkers for ET patients.